Comparative Study of The Effect of Training on Nurses Performance Related To The Safety Targets of Fall Risk Patients at General Hospital Indonesian Christian University Jakarta - dwi rohyani; Sudibyo Supardi; Djuariah Chanafi (Akademi Keperawatan RSPAD Gatot Soebroto, 2020)
Patient’s Safety is part a service system in a hospital to give comfort and protection, so the patient feel more secured. Fall patient’s accident is mostly reported happen to adult patient when they were having a care unit. Patien’s safety training is purposed to add nurses performance motivation to prevent fall patient. This research is meant to see whether there is a connection between the workshop, attitude, motivetion of nurses performance and the patient safety from fall accident in General Hospital Indonesian Christian University, Jakarta. This research used quantitative method combine with comparative study design. This comperative study is conducted by comparing the nurses performance toward patient safety of fall accedent between those who had the trainng workshop and those who dont have the training workshop. The ammount of the sample to this research is 94 respondents, which is divided into two groups. 56 respondents who had the workshop training and 38 respondents who did not have workshop training. Then two these two groups are conducted an osbervation and being compared. The technique of sample taking is using total sampling technique. The result of this research showed that there is an influence of training (p=0,000) motivation (p = 0,010), to patient safety of fall accident prevention OR (Odd Ratio) valvue is 8,603 times higher than to thoses who did not have the patient safety training workshop. This research recommends the necessary to conduct a workshop training to develop attitude, motivation and standarized nurse performance to prevent patient fall accident risk.